Introgression and the current status of the Scottish wildcat (Felis silvestris silvestris) - Kilshaw, K (2015)
Baseline data on a species' distribution and abundance are essential for developing practical conservation management plans. Such data are difficult to obtain for many low density cryptic carnivores. The Scottish wildcat, Felis silvestris silvestris, is no exception with <400 individuals thought to remain. Its conservation has been further complicated by extensive hybridisation and introgression with the domestic cat (F.s.catus). Hybridisation has also resulted in difficulties in discriminating between wildcats, wildcat x domestic hybrids (hybrids) and tabby coloured feral domestic cats. This has inhibited survey efforts, leading to a lack of general ecological information. Using the most recent identification tools available, extensive surveys using various methods including camera trapping were carried out across Northern Scotland in order to examine the current status of the Scottish wildcat. Current distribution indicates a more restricted range than recent studies. Wildcats are at risk of hybridisation from feral domestic cats and in particular, hybrids, throughout their current probable range. The distribution of hybrids overlaps with both feral domestic cats and wildcats, pointing to a significant threat from hybrids acting as a bridge between wildcats and feral cats. Mean density estimates of 3.5 (SD=0.7) wildcats/100 km2 were comparable with those from other studies in Scotland using different survey methods. Total population size estimates ranged between 115-314 individuals depending on local densities and home range size. Population viability analysis (PVA) indicated the current population is not viable unless management actions are undertaken in the near future (Mean time to extinction = 48.2 years (SD = 9.39), probability of extinction=1, SE = 0), and that reducing mortality rates and/or supplementing populations from captive bred cats are likely to be necessary to achieve viability. Based on these data, the Scottish wildcat may be more endangered than many other species classified as Endangered and the current status of the Scottish wildcat should be reviewed.